Total Pesticide Exposure Calculation among Vegetable Farmers in Benguet, Philippines. (20th October 2009) - Lu, Jinky Leilanie
Abstract : This was a cross-sectional study that investigated pesticide exposure and its risk factors targeting vegetable farmers selected through cluster sampling. The sampling size calculated withP = .05 was 211 vegetable farmers and 37 farms. The mean usage of pesticide was 21.35 liters. Risk factors included damaged backpack sprayer (34.7%), spills on hands (31.8%), and spraying against the wind (58%). The top 3 pesticides used were pyrethroid (46.4%), organophosphates (24.2%), and carbamates (21.3%). Those who were exposed to fungicides and insecticides also had higher total pesticide exposure. Furthermore, a farmer who was a pesticide applicator, mixer, loader, and who had not been given instructions through training was at risk of having higher pesticide exposure. The most prevalent symptoms were headache (64.1%), muscle pain (61.1%), cough (45.5%), weakness (42.4%), eye pain (39.9%), chest pain (37.4%), and eye redness (33.8%). The data can be used for the formulation of an integrated program on safety and health in the vegetable industry.